2020
DOI: 10.2196/22740
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital–Accrual, Escape-From-Self, and Time-Displacement Effects of Internet Use During the COVID-19 Stay-at-Home Period: Prospective, Quantitative Survey Study

Abstract: Background COVID-19 has spread like wildfire across the globe, prompting many governments to impose unprecedented stay-at-home orders to limit its transmission. During an extended stay-at-home period, individuals may engage in more online leisure activities. Internet use is a double-edged sword that may have both desirable and undesirable effects on psychological well-being, and this study sought to disentangle adaptive from maladaptive internet use amidst this unusual health crisis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 63 publications
1
34
0
2
Order By: Relevance
“…The role of effective coping in mitigating mental health problems depends largely on the extent to which a deployed strategy meets the specific demands of the stressful encounter concerned. For instance, playing online games or browsing social network sites can be stress-relieving during leisure time (52,53), but prolonged gameplay or social media use can impair work or academic performance while working or studying from home (54). These findings are in line with the theory of coping flexibility, highlighting the beneficial role of flexible coping in soothing mental health problems experienced during the pandemic.…”
Section: Discussionsupporting
confidence: 61%
“…The role of effective coping in mitigating mental health problems depends largely on the extent to which a deployed strategy meets the specific demands of the stressful encounter concerned. For instance, playing online games or browsing social network sites can be stress-relieving during leisure time (52,53), but prolonged gameplay or social media use can impair work or academic performance while working or studying from home (54). These findings are in line with the theory of coping flexibility, highlighting the beneficial role of flexible coping in soothing mental health problems experienced during the pandemic.…”
Section: Discussionsupporting
confidence: 61%
“…In the present digital age, many people deploy information seeking as a coping strategy to mitigate heightened anxiety and gain pragmatic and epistemic control over perceived health threats and uncertainty during the COVID-19 pandemic. Such information-seeking tendencies have been exacerbated by the stay-at-home orders and restrictions implemented in many countries, such as lockdowns, curfews, and teleworking ( 11 ). People also reported expending more effort and time than usual on seeking information through the Internet when living under these measures for disease prevention ( 12 ).…”
Section: Information Seeking As a Coping Strategy And Associated Problemsmentioning
confidence: 99%
“…Researchers have reported evidence of a broad range of benefits to young people associated with the use of SNSs, such as media literacy, creativity, positive education outcomes, civic participation, and well-being (3). There are also findings showing that support and social bond available from online social networking can reduce depressive symptoms, especially during COVID-19 (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…However, intensive involvement in online social networking activities increases the risk of developing problematic SNS use or social networking addiction (SNA) (6). Ample evidence exists to suggest that SNA may lead to a variety of negative psychosocial and physical outcomes (5,7). Researchers also found that adolescents are particularly susceptible to SNA (8) due to their unique developmental characteristics.…”
Section: Introductionmentioning
confidence: 99%